An Assessment of Democracy and Moral Development - Adefarasin, Victor O. (Àgídìgbo: ABUAD Journal of the Humanities, 2018)
This paper argues that democracy has an intrinsic value that has given it a wide acceptance all over the world. Democracy has been conceived as a fundamental creed in order to effectively oppose and overthrow the established order of the Monarchical and Aristocratic rule. But these values are no longer in place due to moral laxity in the society today. The paper discusses meaning and definitions of democracy, fundamental principles of democracy, meaning and definitions of development, theories of development, dimensions of development and features of development. This paper posits further that in today’s society, morality is a necessary factor in the actualization of intrinsic values of democracy. The good of democracy may not be fully actualized where the citizens are not morally developed. It is on this basis, that the citizens should adhere strictly to democratic rules, ethos and principles and these can only be achieved when citizens are morally developed.